Water Retention, Hydraulic Conductivity and Soil-Water Diffusivity of Three Biodraining Sodic Soils as influenced by Concentration and Composition of Water - and S.K. Chaudhari, Poornima Rai, Gopali Bardhan (Journal of the Indian Society of Soil Science, 2014)
Salt-affected soils deteriorate as a result of changes in soil reaction (pH) and in the proportions of certain cations and anions present in the soil solution and on the exchange sites. A laboratory study was carried-out to evaluate the effect of water salinity and SAR on water retention and transmission behavior of three waterlogged sodic soils, subjected to biodrainage. The three sodic soils had ESP of 16.3, 70.5 and 27.4. Very high degree of dispersion (67.2 to 80.9%) was observed in these soils. The pH ranged from 9.06 to 10.9 in soil-water suspension and from 8.25 to 10.0 in saturation paste extract. The highest ESP Plot (70.5) had pH value of 10.9 in soil-water suspension. Sodicity had marked influence on water retention and no change was observed in drainable water, but the available water was considerably influenced by soil sodicity. Concentration and composition of the water flowing through the soil showed a marked influence on saturated hydraulic conductivity of sodic soils. Passing 1 M solution each of NaCl, CaCl2 and MgCl2 gave hydraulic conductivity in the order: CaCl2 > MgCl2 > NaCl suggesting that the Ca2+ salts had positive impact in improving the hydraulic conductivity of sodic soils. Passing mixed salt solutions through these soils also resulted in varying hydraulic conductivity. A water with SAR 5 mmol1/2 L-1/2 and TEC 50 me L-1 resulted in higher saturated hydraulic conductivity as compared to SAR 50 mmol1/2 L-1/2 and TEC 5 me L-1. Unsaturated hydraulic conductivity and soil-water diffusivity also revealed the same trend. Results clearly showed that waterlogged sodic soils are difficult to manage as the high amount of exchangeable sodium deteriorates soil structure and make soil prone to dispersion. For reclaiming these high ESP soils, Ca2+ salts are necessary. Results also hint towards a possibility of use of saline waters on these highly sodic, impermeable soils.